Time‐gated interferometric detection increases Raman scattering to fluorescence signal ratio in biological samples. Issue 1 (1st November 2021) - Ksantini, Nassim; Veilleux, Israel; de Denus‐Baillargeon, Marie‐Maude; Orsini, Patrick; Dicaire, Isabelle; Lecourt, Jean‐Bernard; Gognau, Alexandre; Hernandez, Yves; Baylon, Antonio; Massabki, Maroun; Lesage, Frederic; Leblond, Frederic
Abstract: Attainable levels of signal‐to‐background ratio (SBR) in Raman spectroscopy of biological samples is limited by the presence of endogenous fluorophores. It is customary to remove the ubiquitous fluorescence background using postacquisition data processing. However, new approaches are needed to reduce background contributions and maximize the fraction of the sensor dynamical range occupied by Raman photons. Time‐resolved detection using pulsed lasers and time‐gated measurements can be used to address the signal‐to‐background problem in biological samples by limiting light detection to nonresonant interaction phenomena with relaxation time scales occurring on sub‐nanosecond time scales, thereby excluding contributions from resonant phenomena such as fluorescence. A time‐gated Fourier‐transform spectrometer was assembled using a commercially available interferometer, a single channel single‐photon avalanche diode and time tagging electronics. A time gate of 300 ps increased the signal‐to‐background‐ratio of the 1440 cm −1 Raman band from 36% to 69% in an olive oil sample hereby demonstrating the potential of this approach for autofluorescence suppression. Abstract : Attainable levels of signal‐to‐background ratio (SBR) in Raman spectroscopy of biological samples is limited by the presence of endogenous fluorophores. To address this problem, we combined for the first‐time time‐gated single photon detection and Fourier‐transform Raman spectrometry. With this system, a time‐gate reduction allowed a significant increase of the Raman SBR, hereby demonstrating the potential of this approach for autofluorescence suppression.